Typology of Design Concepts for Luxury Car Showrooms - Jyi, Mervyn Wong Hsin; Atta Idrawani, Zaini; Dona Rose, Amer Koesmeri; Ruzanah, Abu Bakar (2022)
This paper attempts to characterize the typology of luxury car showrooms in Malaysia. The architectural design of luxury car showrooms is subject to changes and development of the economy, technology and behavior of the consumers in the market. It is also dependent on the brand’s Corporate Identity (C.I.), which is formed by cultural adaptations from its country of origin, competitors in the industry and the demands of car owners. Each brand must incorporate their own C.I. into the design of the showrooms to maintain standard requirements and safeguard the outlook and operation of the showrooms. This paper employs a case study approach as its main research method. The study is mainly based on observation on built examples and draws conclusion from the input of architects who are specialized in designing car showrooms in Malaysia. The findings indicate that the design typology of luxury car showrooms is an expression of the values of the brand’s C.I., integrates lounge spaces with the showroom area, constructed with premium quality materials and at times, be shaped by the design guidelines provided by the brands to comply with their international identity.